Насекомые — основные вредители ив в плавневых лесах Украины и меры борьбы с ними - Руднев, Д.Ф.; Карасев, В.С. (Вестник зоологии, 1969)
At present the plavni willow stands of the Ukraine are very damaged with insects. Among them Hiponomeuta rorella H b., Ocneria dispar L., Euproctis chrysorrhoea L., Rhabdophaga rosaria L., Aprophora salicina G о e z e, Lepidosophes ulmi L. and some others are the most distributed.
Willow wood is damaged by Cossus cossus L., Aegosoma scabricornis Scop and Xilotreshus rusticus L. Multiple damages caused by Agrilus ater L. and Poecilonota variolosa P a у k. result in dying off a bark and bast and formation of dead sides in trees.
Application of chemical control in plavni forests is limited. Only those chemical weed- and pest-killers can be used here which are not toxic for men, warm-blooded animals and fish and possessing weak comulative properties. These properties are very pronounced in chlorophos (dipterex), rogor, dimecron, tiocron, nogos, phozalone and cidial which in the experiments on small plots proved to be a high-effective means of willow pest control. Under conditions when the application of chemical weed- and pest-killers is absolutely inadmissible, it is possible to apply entobacterin-3 and cement which gave satisfactory results in combating the Hiponomeuta rorella Hb.